Critical Analysis of Educational Interaction Patterns between Lecturers and Students in the Learning Process - Kurniawati, Luthfiyah (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study aims to critically analyze the patterns of educative interaction between lecturers and students in higher education learning processes, the factors influencing the effectiveness of such interactions, and their impact on student engagement and academic learning outcomes. The research employed a qualitative approach using a descriptive-analytical method. Data were collected through participatory observation, in-depth interviews, and document analysis, and were analyzed using thematic analysis supported by source and method triangulation to ensure data credibility. The findings indicate that lecturer– student educative interaction patterns tend to shift toward two-way interaction, although they are not yet fully consistent and remain largely lecturer-centered, particularly during content delivery. The effectiveness of educative interaction is influenced by lecturers’ pedagogical competence and communication skills, the use of instructional methods and media, and technological support, especially in online and blended learning contexts. Dialogic and responsive interaction patterns were found to have a positive impact on student engagement, conceptual understanding, learning motivation, and the development of critical thinking skills. This study emphasizes that the quality of educative interaction is a key factor in fostering effective, inclusive, and meaningful learning processes in contemporary higher education.